Comparative study on the behaviour of Chitosan-Gelatin based Hydrogel and nanocomposite ion exchanger synthesized under microwave conditions towards photocatalytic removal of cationic dyes. (1st March 2019) - Kaur, Kuljit; Jindal, Rajeev
Graphical abstract: Highlights: CH-GEL/ZSPNC (MW) removed 99% of cationic dye from solution as compared to the parent hybrid polymer network (12%). TEM and AFM results proved the particle size of the synthesized composite was in nano range. Adsorption kinetic data fitted well with non-linear PFO kinetic model. Abstract: The present work reports the comparison study of Chitosan-Gelatin based hydrogels with their nanocomposite ion exchangers synthesized under microwave conditions for the adsorption and photodegradation of the cationic dyes. In this report, the hydrogel based on Chitosan-Gelatin, more selective for anionic dyes is modified to nanocomposite ion exchanger by incorporating the zirconium (IV) selenophosphate to make it selective for cationic dyes. The nanocomposite was investigated with a tremendous hike in the degradation capacity (99% from 12%) of MB after being modified to nanocomposite ion exchanger. Adsorption process followed Langmuir adsorption (Qo = 10.46 mgg −1 ) and non linear PFO kinetic model with k1, qe (calculated), R 2, RMSE = 0.011, 1.02 (mgg −1 ), 0.996, and 0.01709 respectively.